2005
DOI: 10.1074/jbc.m412481200
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of TOM1L1 with the Multivesicular Body Sorting Machinery

Abstract: Tom1L1 (Tom1-like1) and related proteins Tom1 (Target of Myb1) and Tom1L2 (Tom1-like2) constitute a new protein family characterized by the presence of a VHS (Vps27p/Hrs/Stam) domain in the N-terminal portion followed by a GAT (GGA and Tom) domain. Recently it was demonstrated that the GAT domain of both Tom1 and Tom1L1 binds ubiquitin, suggesting that these proteins might participate in the sorting of ubiquitinated proteins into multivesicular bodies (MVBs). Here we report a novel interaction between Tom1L1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
69
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 63 publications
3
69
0
Order By: Relevance
“…At the plasma membrane, CEP55 (19)(20)(21) and the P(S/T)AP motifs of HIV-1 Gag (22)(23)(24)(25) and other viral proteins provide the additional increment in affinity to drive recruitment. In the case of endosomes, the P (S/T)AP of the Hrs subunit of ESCRT-0 and the proteins Tom1L1 and GGA3 could serve as additional factors providing specificity (26)(27)(28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…At the plasma membrane, CEP55 (19)(20)(21) and the P(S/T)AP motifs of HIV-1 Gag (22)(23)(24)(25) and other viral proteins provide the additional increment in affinity to drive recruitment. In the case of endosomes, the P (S/T)AP of the Hrs subunit of ESCRT-0 and the proteins Tom1L1 and GGA3 could serve as additional factors providing specificity (26)(27)(28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Five Ala and/or Gly residues (9,16,28,35) are highly conserved and are involved in the formation of an 'Alanine zipper' between the first two helixes (see Supplementary material Figure S4) [64]. The 'Alanine zipper' also participates in the coiled coil formation as a result of its interaction with aromatic and/or large hydrophobic side-chain residues as Leu, Tyr and Ile.…”
Section: Vps4mentioning
confidence: 99%
“…Also VPS27 and HRS contain clathrin-binding motifs and colocalize with flat 'bilayered' endosomal clathrin coats [26,37,38]. TOM1L1 interacts with HSR and the ubiquitin-binding protein TSG101 of the ESCRT-I complex [28]. Therefore, VSP27, HRS and TOM1 proteins might act as adaptor and concentrator molecules that interact with the flat endosomal clathrin coat and bind to both the monoubiquitinated transmembrane proteins and an ESCRT-I component.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is not known whether Vav proteins have a role in EGFR endocytosis or trafficking. Recently, in a proteomic study on multi-SH3 domain containing proteins, we identified two endosome-associated proteins that interacts with Vav2: the Rab regulatory protein Gapvd1 and the endosome-associated protein Tom1L1 (Puertollano, 2005;Bache et al, 2006;Hunker et al, 2006;Thalappilly et al, 2008). The aim of this work is to better understand the role of Vav2 in EGFR endocytosis and degradation in association with the endosomal proteins (Gapvd1 and Tom1L1).…”
Section: Introductionmentioning
confidence: 99%